Antioxidant and Antimicrobial Activities of Larrea Divaricata Cav. Aqueous Extract on Vitamin C from Natural Orange Juice - Micucci, Patricia Gabriela (2011)
Larrea divaricata Cav. is a South American plant widely distributed in Argentina with reported antioxidant and antimicrobial activities. Vitamin C (Vit C) the most important water-soluble antioxidant, is degraded upon factors such as oxygen, heat, light, storage time and temperature, during cooking and in presence of microorganisms. The aim of this work was: to study the antioxidant and antimicrobial activity of an aqueous extract of L. divaricata (E) on Vit C prepared in water and on Vit C from natural orange juice, submitted to different store conditions such as temperatures and oxygen. The antioxidant activity was determined by DPPH method and used to obtained the relative Vit C concentration; Vit C decreased its activity and concentration under temperature and air oxygen, but E allowed Vit C to recover its antioxidant activity and prevented Vit C microorganism contamination. These studies were performed in view to establish whether L. divaricata can be used as a supplement on orange juices capable to prevent Vit C decay and microbial growth.